The relationship of undergraduate students' lifestyle and the impact to students' health - Mohamed Elias, Ezanee; Abu Bakar, Haniff Suhairi; Mahidin, Norlila; Kim, Ji Fang; Abu Bakar, Siti Zakiah (Advance Scientific Research, 2020)
As the academic standards are becoming more competitive, students in universities have a more challenging lifestyle due to hectic academic schedules, rules and regulations and extracurricular activities. Many students develop a series of unhealthy behaviors, such insufficient nutrition, lack of rests and physical activities. Students with an unhealthy lifestyle commonly have less nutrients and low physical activity are identified be more depressed and weaker in mind and physique. Past studies show that unhealthy students are more likely to deal with difficulty in learning and thus impacted the achievement, attendance, and academic performance. In the long-run, unhealthy lifestyle inherits from university will affect the student’s quality of life. Hence, this study examines the wellness factors among undergraduate students in a northern state of Malaysia. A total of 1436 undergraduate students from three colleges; COB, COLGIS and CAS were randomly selected to answer the survey questionnaire via online form. The data collected was analyzed by SPSS software. Our findings show variables like the unhealthy lifestyle, food consumption and lack of physical exercise have a significant relationship to the students’ health problem including the academic results. Therefore, the university’s top management perhaps need to inspire their students to improve health condition and well-being to pursue better performance in academic. *CRITICAL: Do Not Use Symbols, Special Characters, Footnotes, or Math in Paper Title or Abstract. (Abstract)